Pengaruh Pelatihan Sumber Daya Insani Terhadap Kinerja Karyawan BMT-UGT Sidogiri di Surabaya dan Sidoarjo - Azizah Nur Rahmayani; Ari Prasetya (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purposes of employees training are to improve, develop, and enhance their skills. In an organization, the scoring of employees’ performance has very essential role in making decision effectively related to the whole process of human resource management. This research purposes to reveal how far the training influences the performance of employees of BMT Sidogiri in Surabaya and SidoarjoThis research used quantitative approach with saturated sampling method (atechnique of sampling if the entire member of population is used). Consequently it is called census research. It investigates 34 employees who work as account officer. Data collected with questionnaires and analyzed with multiple linier regression.The result of this research shows the human resource training variable simultaneously and reliably can influence the employees’ performance based on the result of F test is 65,390 with significance level is 0,000. The contribution of human resource training is 92.1% with the rest is the other variables. Partially, all human resource variable influences to the employees’ performance according to t test result (the each level of training instructor variable, training participants variable, training method, training material, and training facility is less than 0,05). Training facility is the dominant variable regards to the employees’ performance with 0,374 beta level. REFERENCESAl Tirmizi. 1993. Sunan Al Tirmizi, Kuala Lumpur, Victory Agency.Alma, Buchari., Donni Juni Priansa. 2009. Manajemen Bisnis Syariah. Penerbit Alfabeta. Bandung.Al-Mawdudi, Abu al-A'la. 1967. Islamic Way of Life. Delhi: Markazi Maktaba Islami.Anindya, Tiara.V. 2011. Pengaruh Fungsi Sosial Terhadap Citra Perusahaan dan Istiqomah pada Nasabah Bank Syariah Mandiri di Surabaya. Skripsi Tidak Diterbitkan. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Asse, Ambo. 2010. Konsep Adil dalam AlQur’an. Al- Risalah. Vol. 10 No. 2.Baron dan P. David. 2006. Business and It’s Enviroment. Edisi ke-5. UpperSaddle River, New Jersey: Pearson Education Inc.Carroll dan B. Archie. 1999. Corporate Social Responsibility. Business and Society. Chicago. Vol.38, September.Chapra, M.U. 1992. Islam and the Economic Challenge. Herndon, VA.Dusuki, Asyraf Wajdi & Nurdianawati, Irwani Abdullah. 2005. Maqashid al-shari’ah, Maslahah, dan Corporate Social Responsibility. The American Journal of Islamic Social Sciences. Vol. 24 No.1.Elkington, J. 1997. Cannibals with Forks: The Triple Bottom Line of 21st Century Business. Capstone. OxfordFarook, Sayd. 2007. On corporate social responsibility of Islamic financial institutions. Islamic Economic Studies. Vol. 15 No.1: 32-46Griffin, W. Ricky, Ebert dan J. Ronald. 1996. Bussiness. Edisi ke-5. Mc Graw Hill.Juhaya, S. Praja. 1995. Filsafat Hukum Islam, LPPM Unisba, Bandung, IndonesiaKotler, Philip and Lee, Nancy. 2005. Corporate social responsibility: doing the most good for your company and your cause. New Jersey: John Wiley and Sons, IncMalik. 1951. Al-Muwatta. Kairo, Malik, v.2, h.980: 40Mohammed, J. A. 2007. Corporate social responsibility in Islam. Doctoral dissertation, AUT UniversitySalim, Abd. Muin. 1994. Fiqh Siyasah Konsepsi Kekuasaan Politik dalam Al-Quran. Jakarta: LSKIShihab, M. Quraish. 1996. Wawasan AlQur‟an Tafsir Maudhu‟i atas Pelbagai Persoalan Umat. Bandung: Mizan.Steiner A. George dan F. John. 1994. Business, Goverment and Society: AA managerial Perspective. Edisi ke-7. McGraw-Hill International Edition.Suharto, Edi. 2010. CSR&COMDEV Investasi kreatif perusahaan di era globalisasi. Bandung: AlfabetaWibisono, Yusuf. 2007. Membedah konsep dan aplikasi CSR. Gresik: Fascho PublishingYusuf, Muhammad Y., & Zakaria Bahari. 2011. Islamic Corporate Social Responsibility in Islamic Banking: Towards Poverty Alleviation. International Conference on Islamic Economics and Finance. Vol. 10.